2017
DOI: 10.1039/c7ra02689g
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of hexabromocyclododecane (HBCD) by grinding assisted with sodium persulfate

Abstract: Hexabromocyclododecane (HBCD) has been widely used as a flame retardant in polystyrene and textiles, and is ubiquitous in all kinds of environmental media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, addition of strong bases or electron donors (e.g., Fe) has been proved to remarkably accelerate persulfate cleavage kinetics and, consequently, target organics mineralization rate. Experiments on hexabromocyclododecane MCD (Figure 4b) [35] revealed that the meager debromination capability of persulfate could be markedly improved by addition of $20% NaOH. Then, excessive NaOH interfered with sulfate generation (likely by reacting with sulfate radical), reducing the debromination rate to levels close to those obtainable by treatment with sole NaOH.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, addition of strong bases or electron donors (e.g., Fe) has been proved to remarkably accelerate persulfate cleavage kinetics and, consequently, target organics mineralization rate. Experiments on hexabromocyclododecane MCD (Figure 4b) [35] revealed that the meager debromination capability of persulfate could be markedly improved by addition of $20% NaOH. Then, excessive NaOH interfered with sulfate generation (likely by reacting with sulfate radical), reducing the debromination rate to levels close to those obtainable by treatment with sole NaOH.…”
Section: àmentioning
confidence: 99%
“…Figure 4.Influence of multi-reagent composition on two MCD systems: (a) hexachlorobenzene high-energy milled withFe-SiO 2[17], and (b) hexabromocyclododecane high-energy milled with Na 2 S 2 O 8 -NaOH[35].…”
mentioning
confidence: 99%
“…Previous reports have shown that TCPP is both carcinogenic and teratogenic and accumulates in the liver and kidneys, resulting in a decrease of the number of cells and a change in neurotransmitters (Hoffman et al, 2014). Mechanochemical (MC) destruction is an effective and environmentally friendly method of removing chlorinated organic pollutants (Yan et al, 2017). Unlike photocatalytic and microbial degradation (Jurgens et al, 2014, Ruan et al, 2013, MC degradation is inexpensive, rapid, efficient, produces harmless degradation products (Cagnetta et al, 2016) and has been used for the degradation of persistent organic pollutants (Veen & Boer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Metals and metal oxides have been used as co-milling reagents to enhance the efficiency of the MC process in ball-milling (Fan et al, 2018, Yan et al, 2017. As a strong oxide, persulfate is widely used in the degradation of organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Also, persulfate can be activated by MC process with NaOH or CaO to degrade organic pollutants (Fan et al, 2020, Yan et al, 2015. Previous studies have shown that zero-valent iron (ZVI), Fe 2+ and Fe 3+ can activate persulfate (Oh et al, 2009, Wei et al, 2016, Yan et al, 2017. Under the action of free radicals, the C-Cl bonds of organic pollutants are broken and organic substances gradually become inorganic substances, eventually resulting in mineralization (Cagnetta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%